Pakaian Muslim: Keseimbangan Antara Syariah dan Mode (Interpretasi QS. Al-A’raf [9]: 26 Dengan Pendekatan Semiotika Saussure) - Satria Tenun Syahputra (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
Muslim clothing is not only about covering the aurat, but there is one more important essence behind clothing, namely to beautify the appearance or in contemporary language also called fashion. This research is a library research that is analytical-critical by analyzing QS. Al-A'râf [9]: 26. The surgical instrument used in this study is Ferdinand D Saussure's semiotic approach which is also known as binary opposition, but only one pair of binary oppositions is used, namely langue and parole. From this research, it is stated that maintaining a balance between the main purpose of clothing as an aurat cover with secondary purposes as decoration, fashion and appearance support is the guidance of the Quran. This approach needs to be developed to gain an understanding that is in accordance with the development of the times and science and is in line with the cosnep Universality of the Quran which carries the concept of